Enhanced hole extraction by electron-rich alloys in all-inorganic CsPbBr3 perovskite solar cells. Issue 61 (12th July 2021) - Zhao, Yuanyuan; Zhu, Jingwei; He, Benlin; Tang, Qunwei
Abstract : Electron-rich Pt3 M alloy is incorporated into carbon electrode to maximize hole extraction in all-inorganic CsPbBr3 perovskite solar cells. Abstract : We present the fabrication of electron-rich Pt3 M alloy-tailored carbon electrodes to maximize hole extraction. Through optimizing the doses and alloy species systematically, the best all-inorganic CsPbBr3 perovskite solar cell achieved a power conversion efficiency of 9.08% and showed excellent long-term stability at 80% RH over 20 days.